CENTRAL ASIA IN SEARCH OF STABILITY - Plastun, Vladimir (CENTRAL ASIA AND THE CAUCASUS, 2008)
The tension in the Central Asian Region, particularly in its southern part, which includes Afghanistan, Pakistan, and Iran, largely affects the rest of this vast area and forces the United States and its allies to seek prompt settlement of the crisis they have on their hands. The situation in occupied Iraq is tense; the Turkish invasion into Iraqi Kurdistan in search of terrorists of the Kurdistan Workers’ Party did nothing to relieve the tension; the conflict area spread even further. Two other events (the state of emergency President of Pakistan Musharraf introduced on 3 November, 2007, allegedly as an antiterrorist and anti-extremist measure, and the death of Benazir Bhutto at the hands of terrorists) brought the tension to boiling point.About twelve months ago, two fairly prominent people—James Jones, NATO commander in 2003-2007, and Mansour Ijaz, who in 2000 initiated a ceasefire between the mojaheddin and the Indian troops in Kashmir—offered their opinions on the continued conflict and possible solutions in The Financial Times. “Pakistan and Afghanistan stand at a dangerous crossroads in their complex and troubled relationship. Both strong allies of the U.S. in its war to eradicate terrorism, Afghanistan is laboring to find stability under NATO mandate while Pakistan is struggling to find a balance between national interest and regional responsibilities to fight extremists on its own soil. Sadly, Afghanistan is losing its struggle for stability and security in part because Pakistan cannot decide whether it wants to fight terrorism or encourage it as state policy.”This suggests that Pakistan is held responsible for the dangerous situation in Afghanistan. Its leaders tend to encourage and/or ignore the Taliban’s armed inroads from Pakistan’s border areas into Afghanistan. This has already caused numerous complaints from the United States, NATO, and the Afghan government.What is behind Pakistan’s puzzling behavior? It looks very strange in light of the incessant references to the “fraternal peoples” of both countries and their “centuries-long friendship” that are invariably made at all the………….